Web software to create thematic maps for precision agriculture - Borges, Ligia Francielle; Bazzi, Claudio Leones; Souza, Eduardo Godoy de; Magalhães, Paulo Sergio Graziano; Michelon, Gabriela Karoline (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to develop and provide a free web application able to generate thematic maps. The initiative aims to incorporate the functionalities of the “Software para Definição de Unidades de Manejo” (SDUM) desktop application, which has proven to be suitable for working with thematic maps and management zones, but that was only available for desktop computers. The developed web application was tested with real data from two agricultural fields located in the state of Paraná, Brazil. Thematic maps of soil and plant characteristics relevant to precision agriculture were created through the following interpolation methods: inverse distance, moving average, and nearest neighbor. The obtained results show that the usage of this web tool allows identifying areas with the same behavior toward soil variables, making it possible for the user to have a better and more accurate vision of the area to be worked on and to identify possible causes of variation in productivity. Because it is installed in a server with on-demand features, the software has a satisfactory performance from a functional point of view and can be accessed from any web environment.